Unlocking the Curtain of Confidence: Drama in Education Breathing Life into Spoken English Skills for Elementary School Pupils - Li , Peiyan (Journal of Theory and Practice of Contemporary Education, 2023)
Drama in education is a pedagogical approach that utilizes theatrical techniques and activities to enhance learning experiences. Numerous studies have highlighted the benefits of incorporating drama into educational settings, particularly in the field of primary school oral English teaching. However, traditional English teaching method in China limit students' development in speaking English. Therefore, this essay is trying to take M elementary school as a case, through an empirical study and show the realistic transformation of the British and American experience in the Chinese practice of drama in education is presented.